P48 An evaluation to understand the use of technology within a COPD population. (14th November 2013) - Gibb, M; Willott, V; Lohar, S; Ward, S; Bolton, C; McAlinden, P; De-Soyza, A; Singh, S
Abstract : Introduction and Objectives: There is a desire to employ technology to support patients with long term conditions. However there is little data available that describes familiarity with technology in the COPD population. We have an interest in developing alternative forms of pulmonary rehabilitation deploying technology. Therefore the aim of this evaluation was to understand the use of technology in this population. Methods: Patients attending a consultant led COPD follow up clinic were asked to fill out a 10 itemed survey regarding their physical activity levels, if they had an interest in pulmonary rehabilitation and technological devices they may use. Results: 191 patients returned the surveys, 168 from the Glenfield Hospital Leicester and 23 from the Newcastle upon Tyne Hospitals. The population surveyed consisted of 76 males, 81 females and 34 who did not specify their gender. The age range of population was; <40 yrs 14 (8%); 40–50 yrs 18 (9.6%); 50–60 yrs 29 (15.5%); 60–70 yrs 61 (32.6%); 70–80 yrs 47 (25.1%); > 80yrs 17 (9.1%). Within the total population it was found that 112 (60.5%) owned a computer and 138 (74.2%) own a mobile telephone however, of 138 only 22 (11.8%) were owners of a smart phone. Within each age range there were a small number of smart phone users but the predominant usage of smart phones occurred within the younger age ranges. Furthermore, within each age range a higher percentage of the population owned a mobile phone than those that did not. Similarly within each age range a higher percentage of the population owned a computer than did not, excluding the >80 yrs, where 9 (52.9%) did not own a computer. Conclusion: Overall the use of technology is limited in this COPD population. A significant proportion of those taking part used a mobile phone but a very small percentage used a smart phone, upon which a number of interventions might be delivered. Over half the population had a computer. There is a potential target market for providing alternative forms of pulmonary rehabilitation utilising technology, however, more evaluation is needed to ascertain whether a technological intervention would be acceptable to these patients.